Aortic dissection induced by vascular endothelial growth factor inhibitors - Dai, Shuqi; Zhong, Yu; Cui, Hongxia; Zhao, Jin; Li, Su (Frontiers in Pharmacology, 2023)
Vascular endothelial growth factor (VEGF) contributes to angiogenesis and vasculogenesis. The occurrence and progression of tumors are accompanied by angiogenesis. Vascular endothelial growth factor inhibitors (VEGFI) have been used in anti-tumor treatment. However, aortic dissection (AD) is one of the VEGFI-associated adverse reactions with cute onset, rapid progression, and high case fatality rate. We collected case reports of VEGFI related to aortic dissection in PubMed and CNKI (China National Knowledge Infrastructure) from inception to 28 April 2022. Seventeen case reports were selected. The medication included sunitinib, sorafenib, pazopanib, axitinib, apatinib, anlotinib, bevacizumab, and ramucirumab. This review discusses the pathology, risk factors, diagnosis, and treatment of AD. Vascular endothelial growth factor inhibitors are related to aortic dissection. Although current literature lacks clear statistical evidence on the population, we offer points to encourage further confirmation of the best methods of care for these patients.